Finite Element Analysis of Plate Structure Excited by Patches of Piezoelectric Actuators - Mohd Najib , Ali Mokhtar; Fairul Azni , Jafar (2011)
Active damping using piezoelectric element is one of the effective technique to counter vibration problems. A 3D finite element model is developed as part of investigation for active damping control. The piezoelectric are surface bonded with quadrilateral thin plate and supported with spring damper elements. This simulation project focuses on analysis of the piezoelectric actuators to achieve active damping on plate structure at low frequency spectrum. By numerical simulation the effect of the system in actuator mode at appropriate electric excitation from piezoelectric actuator are investigated. The force induced by piezoelectric actuator under certain applied voltage fields is used as load. Natural frequency of the system and corresponding mode shape are presented and the double symmetric mode shapes are examined. The result can be used as reference or validation of optimal locations and configuration of the piezoelectric patches for active damping control system.